Anatomical Comparison of Antennal Lobes in Two Sibling Ectropis Moths: Emphasis on the Macroglomerular Complex - Liu, Jing; He, Kang; Luo, Zong-xiu; Cai, Xiao-ming; Bian, Lei; Li, Zhao-qun; Chen, Zong-mao (Frontiers in Physiology, 2021)
Ectropis obliqua and Ectropis grisescens are two sibling moth species of tea plantations in China. The male antennae of both species can detect shared and specific sex pheromone components. Thus, the primary olfactory center, i.e., the antennal lobe (AL), plays a vital role in distinguishing the sex pheromones. To provide evidence for the possible mechanism allowing this distinction, in this study, we compared the macroglomerular complex (MGC) of the AL between the males of the two species by immunostaining using presynaptic antibody and propidium iodide (PI) with antennal backfills, and confocal imaging and digital 3D-reconstruction. The results showed that MGC of both E. obliqua and E. grisescens contained five glomeruli at invariant positions between the species. However, the volumes of the anterior-lateral glomerulus (ALG) and posterior-ventral (PV) glomerulus differed between the species, possibly related to differences in sensing sex pheromone compounds and their ratios between E. obliqua and E. grisescens. Our results provide an important basis for the mechanism of mating isolation between these sibling moth species.